1988
DOI: 10.2134/agronj1988.00021962008000060018x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Maize to Plant Population Density. I. Canopy Development, Light Relationships, and Vegetative Growth

Abstract: Understanding of maize (Zea mays L.) canopy structure and light transmission over a wide range of plant population densities (PPD) is necessary in the formulation of maize intercrop associations. Experiments using a systematic (fan) design were conducted on Lake fine sand (hyperthermic, coated Typic Quartzipsamments) at Gainesville, FL (29°38′N), in 1985 and 1986 to assess the interrelationships among maize canopy structure, light interception, and vegetative growth over 15 PPD (0.8 to 15.4 plants m−2). Fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
106
1
7

Year Published

1992
1992
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(129 citation statements)
references
References 11 publications
15
106
1
7
Order By: Relevance
“…Similar to prior research, this experiment found that morphological traits and ear characteristics are affected by crop density [13,22,26]. Averaged across all hybrids, plant height and ear height increased with higher densities, while tiller number decreased ( Figure 1).…”
Section: Discussionsupporting
confidence: 83%
“…Similar to prior research, this experiment found that morphological traits and ear characteristics are affected by crop density [13,22,26]. Averaged across all hybrids, plant height and ear height increased with higher densities, while tiller number decreased ( Figure 1).…”
Section: Discussionsupporting
confidence: 83%
“…density resulted in increased yield. A further increase in FPP from medium to high (6.4 plants m -2 ) resulted in a decline in GY in agreement with reports by Edmeades and Daynard (1979a), Tetiokago and Gardner (1988), Echarte et al (2000), and Sangoi et al (2002). For each production system there is a population that maximizes the utilization of available resources, allowing the expression of maximum attainable GY on the environment.…”
Section: Discussionsupporting
confidence: 89%
“…However, information on photomorphogenic responses in maize is limited to seedling stages, where shoot stature is increased by low R to FR ratio (Smith, 1980;Kasperbauer and Karlen, 1994). When maize plants are grown in the field, tillering only takes place at low plant densities (Ͻ3.5 plants m Ϫ2 ), suggesting that small reductions in R to FR ratio could severely reduce tillering in this species (Tetio-Kagho and Gardner, 1988).…”
mentioning
confidence: 99%